Detection and interpretation of clouds types using visible and infrared satellite images - Ghazal, Nawal K. (Iraqi Journal of Physics, 2019)
One of the most Interesting natural phenomena is clouds that have a very strong effect on the climate, weather and the earth’s energy balance. Also clouds consider the key regulator for the average temperature of the plant. In this research monitoring and studying the cloud cover to know the clouds types and whether they are rainy or not rainy using visible and infrared satellite images. In order to interpret and know the types of the clouds visually without using any techniques, by comparing between the brightness and the shape of clouds in the same area for both the visible and infrared satellite images, where the differences in the contrasts of visible image are the albedo differences, while in the infrared images is the temperature differences. The data are taken by (MODIS), (GOES) and (METEOSAT) because these satellites are forecasting in a near lifetime data. The case studied in 24/12/2016 over the area of Iraq.